Antiproliferative Activity of Functionalized Histidine‐derived Au(I) bis‐NHC Complexes for Bioconjugation. Issue 17 (31st July 2020) - Jakob, Christian H. G.; Dominelli, Bruno; Hahn, Eva M.; Berghausen, Tobias O.; Pinheiro, Teresa; Marques, Fernanda; Reich, Robert M.; Correia, João D. G.; Kühn, Fritz E.
Abstract: A series of histidine derived Au(I) bis ‐NHC complexes bearing different ester, amide and carboxylic acid functionalities as well as wingtip substituents is synthesized and characterized. The stability in aqueous media, in vitro cytotoxicity in a set of cancer cell lines (MCF7, PC3 and A2780/A2780cisR) along with the cellular uptake are evaluated. Stability tests suggest hydrolysis of the ester within 8 h, which might lead to deactivation. Furthermore, the bis ‐NHC system shows a sufficient stability against cysteine and the thiol containing peptide GSH. The benzyl ester and amide show the highest activity comparable to the benchmark compound cisplatin, with the ester only displaying a slightly lower cytotoxicity than the amide. A cellular uptake study revealed that the benzyl ester and the amide could have different intracellular distribution profiles but both complexes induce perturbations of the cellular physiological processes. The simple modifiability and high stability of the complexes provides a promising system for upcoming post modifications to enable targeted cancer therapy. Abstract : Novel histidine‐derived Au(I) bis ‐NHCs with different functional groups (ester, amide and carboxylic acid) show antiproliferative activity in MCF7, PC3 and A2780/A2780cisR cancer cell lines. A cellular uptake study revealed that the ester and the amide could have different intracellular distribution profiles but both complexes induce perturbations of the cellular physiological processes.